The role of academy in increasing generation awareness on environmental function. (February 2019) - Wijaya, R S; Ulfa, M; Husniah, W O; Syamsurijal, S; Ali, A M; Yahya, S; Hanifa, L; Mahmuda, D; Sujana, I W; Abdullah, R; Adan, L M H; Sadat, A; et al.
Abstract: Difficulty in building human awareness on environmental impacts makes some academics must take concrete steps and actions for the generation's knowledge on the importance of the environment from an early age. Much involvement of elements or elements in increasing environmental awareness makes the final results less efficient/optimal and unsatisfactory. For this reason, the participation of academics in providing this awareness regarding the environmental management needs to be specific to communities that are directly influential and related. The method used was survey research with 376 research samples consisting of students, students and the community (parents) who have a generation awareness of environmental functions. Survey research collected data from respondents by measuring or estimating as a way of conducting observations where indicators about variables are answers to questions given to respondents both verbally and in writing. Academics role in improving understanding of self-awareness will colour all instruments of education level in order to prepare young people who are aware of environmental impacts. Awareness raising of the environment becomes values that internalized in everyday life. Thus, the young generation that has the conscious ability to protect the earth that we inhabit must be developed to face various technological and industry challenges. The conclusions of the study can provide valuable data and information on shared responsibility for managing, utilizing, and tackling the impacts caused by the environment for generations to survive.